Cephasinenoside A, a new cephalotane diterpenoid glucoside from Cephalotaxus sinensis. Issue 43 (24th October 2019) - Zhao, Chun-Xue; Li, Bing-Qian; Shao, Zhao-Xiang; Li, Da-Hong; Jing, Yong-Kui; Li, Zhan-Lin; Hua, Hui-Ming
Graphical abstract: Cephasinenoside A is the first cephalotane diterpenoid glucoside isolated from Cephalotaxus sinensis . It was active against HL-60 cells with GI50 value of 7.17 ± 1.03 μM. The structure including absolute configuration was elucidated based on spectroscopic analyses and calculated ECD methods. Highlights: Cephasinenoside A, a trace constituent identified from the twigs and leaves of Cephalotaxus sinensis. Cephasinenoside A is the first cephalotane diterpenoid glycoside from Nature. The structure was identified by spectroscopic analyses as well as calculated ECD methods. Cephasinenoside A showed potent growth inhibition in HL-60 cells with a GI50 value of 7.17 ± 1.03 μM (VP16: 0.08 ± 0.01 μM). Abstract: A new cephalotane diterpenoid glucoside, cephasinenoside A (1 ), was isolated from the twigs and leaves of Cephalotaxus sinensis (Rehd. et Wils.) Li. The structure of1 was established on the basis of spectroscopic analyses and ECD calculations. Compound1 represents the first cephalotane diterpenoid glycoside which inhibits the proliferation of human acute myeloid leukemia HL-60 cells with a GI50 value of 7.17 ± 1.03 μM.